Twentieth Century Narrative versus Performative Questioning of Historical Representation: Is History a Narrative or a Performance? - Čale-Feldman, Lada (1998)
The theory of historiographic meatafiction deals with the similarities between historiographic and fictional narrative texts. This paper demonstrates that there is an equallz interesting genre of historiographic metadrama/metatheatre, which are based on the metaphorical association between the historical course and theatrical preformance.